ANALISIS KANDUNGAN KARBON PADA KERAPATAN VEGETASI MANGROVE ALAMI DAN REHABILITASI DI SUAKA MARGASATWA KUALA LUPAK - Putri, Rieska Paramita Nilateja; Rifa’i, Muhammad Ahsin; Asy’ari, Mufidah; Fatmawati, Fatmawati (Universitas Lambung Mangkurat, 2023)
Global warming is one of the principal environmental issues that have a major impact on the world and life. One of the principal causes of global warming is the increase in greenhouse gases such as carbon dioxide. The mangrove forest is a carbon-absorbing area. The Kuala Lumpur wildlife reserve includes a representative of the mangrove forest-forest ecosystem with the conservation area that boasts natural mangrove forest vegetation and rehabilitation mangroves. The study aims to estimate biomass and carbon content on the natural mangrove vegetation and rehabilitation in the Kuala Lumpur wildlife reserve. The variables observed are mangrove vegetation (natural and rehabilitation), the level of severity (seldom, moderate, dense) as much as 3 times of the deuteronomy of mangrove vegetation (1a, 2a, 3a) and the mangrove rehabilitation (1b, 2b, 3b). Biomass measurements use allometric equations with carbon content obtained from biomass by 47%. The results showed the average biomass in the natural mangrove region at 434.3 tons /ha and in the rehabilitation area had an average of 11 tons /ha. Whereas the average carbon content in natural mangrove is 204.1 tons /ha and at the rehabilitation area of 5.2 tons /ha.